Tren kenaikan suhu permukaan laut pada abad ke-14 berdasarkan data geokimia Sr/Ca dari fosil koral Mentawai - Cahyarini, Sri Y. (Indonesian Journal on Geoscience, 2010)
DOI:Â 10.17014/ijog.v5i2.96Sr/Ca content ratio in coral is a promising tool for a sea surface temperature reconstruction. In this study, Sr/Ca was analyzed from the top core of fossil coral from Central Mentawai, Indonesia (BLS). The dating of U/Th is used for the age determination of the fossil coral. Based on the U/Th dating, the fossil coral used in this study was deposited in 14th century which approximately has a time range 11 years. The result of this study shows that in the 14th century, the sea surface temperature increased by 3.20 C during 11 years period.